PRE-EXAMINATION STRESS IN SECOND YEAR MEDICAL STUDENTS IN A GOVERNMENT COLLEGE - Rizvi, Areeba Husain; Awaiz, Maha; Ghanghro, Zohra; Jafferi, Mehjabeen Ahmed; Aziz, Sina (Journal of Ayub Medical College Abbottabad, 2010)
Background: Pre-examination Stress is a common condition faced by students prior to exams and is quite predominant among medical students. Many studies have been conducted to assess the impact of stress on students prior to examinations. This study however aims to determine the behavioural and physiological changes occurring in the second year medical students during the pre-examination period. Methods: Questionnaires were distributed among students to review the changes that occurred in medical students related to their behaviour, physical activities and functions just before exams. Duration of study was two months from October-November, 2009. The questionnaire was divided into two parts. The first part contained demographic information about the patient, the second part contained opinions of students experiencing pre-examination stress. SPSS was used for data management and approval from the Ethical Review Board of Dow University of Health Sciences was obtained before starting the research. Results: The data for this study was collected from 226 students of 2nd year MBBS, Dow Medical College, Karachi on specially designed questionnaires. Among the 226 students 22.1% were male while 77.9% were female with mean age 20±1 years. Changes observed in pre-examination period included anorexia, nausea, fatigue (54.87%), changed concentration span (80.09%), increased irritability (68.14%), mood swings (50.88%), disturbed menstrual cycle (15.91%), disturbed sleep cycle (80.97%), increased intake of caffeine/energy drinks (38.94%), disturbed metabolism (46.02%), aggravated skin problems such as acne (12.83%). Among the 226 students 42.04% did regular exercise and 76.12% prayed regularly. Both of these factors helped them in coping with stress. Conclusion: Majority included in our research experienced stress prior to exams but the signs and symptoms varied greatly. Irritability, increased intake of caffeine/energy drinks, and disturbed sleep cycle seemed to dominate physiological and behavioural changes in the pre-examination period. Keywords: Behavioural changes, Physiological changes, Pre examination period, Medical students